Psychotherapy: A World of Meanings - Locher, Cosima; Meier, Sibylle; Gaab, Jens (Frontiers in Psychology, 2019)
Despite a wealth of findings that psychotherapy is an effective psychological intervention the principal mechanisms of psychotherapy change are still in debate. It has been suggested that all forms of psychotherapy provide a context which enables clients to transform the meaning of their experiences and symptoms in such a way as to help clients to feel better, and function more adaptively. However, psychotherapy is not the only healthcare intervention that has been associated with ‘meaning’: the reason why placebo have effects has also been proposed to be a ‘meaning response’. Thus, it has been argued that the meaning of treatments has a central impact on beneficial (and by extension, negative) health-related responses. In light of the strong empirical support of a contextual understanding of psychotherapy and its effects, the aim of this conceptual analysis is to examine the role of meaning and its transformation in psychotherapy – in general – and within three different, commonly-used psychotherapy modalities.